Probing amyloid fibril secondary structures by infrared nanospectroscopy: experimental and theoretical considerations. Issue 1 (27th October 2020) - Waeytens, Jehan; Mathurin, Jérémie; Deniset-Besseau, Ariane; Arluison, Véronique; Bousset, Luc; Rezaei, Human; Raussens, Vincent; Dazzi, Alexandre
Abstract : AFM-IR is a technique that is able to characterize amyloids, but the presence of potential artefacts is discussed to improve structure determination. Abstract : Amyloid fibrils are composed of aggregated peptides or proteins in a fibrillary structure with a higher β-sheet content than their native structure. Attenuated total reflection Fourier transform infrared spectroscopy only provides bulk analysis of a sample therefore it is impossible to discriminate between different aggregated structures. To overcome this limitation, near-field techniques like AFM-IR have emerged in the last twenty years to allow infrared nanospectroscopy. This technique obtains IR spectra with a spatial resolution of ten nanometres, the size of isolated fibrils. Here, we present essential practical considerations to avoid misinterpretations and artefacts during these analyses. Effects of polarization of the incident IR laser, illumination configuration and coating of the AFM probes are discussed, including the advantages and drawbacks of their use. This approach will improve interpretation of AFM-IR spectra especially for the determination of secondary structures of species not accessible using classical ATR-FTIR.